Viden, værdi og omstridt ekspertise: Analyse af den danske debat om lægemiddelprioritering - Wadmann, Sarah (Politik, 2017)
This article explores an ongoing attempt to introduce health economic evaluation in the assessment of newly marketed pharmaceuticals in Denmark. Drawing on valuation theory from the field of science and technology studies (STS), the purpose is to analyse how various conceptions of value interact in the public debate, and how it shapes the political solutions. Building on document analysis, the article shows how actors in the debate express contrasting conceptions of what constitutes relevant expertise, proper mechanisms of resource allocation and a legitimate basis for political decisions. In an attempt to accommodate the dissonance, the resulting decision-model has introduced new challenges for the health authorities to deal with. In particular, a somewhat paradoxical situation has arisen where evaluation institutions are required to undertake evaluations of treatment costs – but without the option of using well-established health economic methods to judge the cost-effectiveness. Hence, evaluation institutions are left with the challenge of how to operationalise the decision-model.